The Utilization of Wuluh Starfruit for Making Facial Cleansing Solid Soap - Dian Maulina; Riski Sartika (Jurnal Inotera, 2021)
Belimbing wuluh is one of the species in the family (Averrhoa). It is estimated that this plant comes from tropical America, this plant grows well in its country of origin, while Indonesia is mostly kept in the yard and sometimes grows wild in the fields or forest edges. In general, wuluh starfruit for the people of Aceh is used as a spice called sunti acid. Starfruit can also be used as a raw material for making soap which has properties to inhibit premature aging and overcome acne problems because starfruit contains vitamins A and C.Belimbing wuluh is also known as a plant that grows in the yards of Acehnese houses, which every time it bears fruit it will produce quite a lot of fruit, if it is not used for making processed products, the fruit will rot on the tree or fall on the ground. Based on the abundant raw materials, this research will focus on "Utilization of Starfruit for Making Facial Cleansing Solid Soap". The purpose of this research is to make solid soap with additional ingredients of starfruit, and produce solid facial soap from starfruit in the form of face wash sticks so that it is easy to use. The research method used is an experimental method which produces three samples that meet the 2016 SNI standard with a moisture content of 10% and a degree of acidity (pH) 10. From the three samples, the first sample had a hardness that matches the characteristics of solid soap.